2017
DOI: 10.1371/journal.pone.0167770
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Cost-Effectiveness of One-Time Screening and Treatment for Hepatitis C in Korea

Abstract: Background and AimsThis study aims to investigate the cost-effectiveness of a one-time hepatitis C virus (HCV) screening and treatment program in South Korea where hepatitis B virus (HBV) prevails, in people aged 40–70, compared to current practice (no screening).MethodsA published Markov model was used in conjunction with a screening and treatment decision tree to model patient cohorts, aged 40–49, 50–59 and 60–69 years, distributed across chronic hepatitis C (CHC) and compensated cirrhosis (CC) health states… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 38 publications
1
43
0
Order By: Relevance
“…One-off HCV screening and treatment of people aged 40-70 years is likely to be very cost-effective compared with the current practice of no screening. 409 Importantly, to reduce the incidence of HCV-related endstage liver-related complications and mortality, a national screening programme should include a national health policy aimed at managing HCV in the South Korean population.…”
Section: The Lancet Gastroenterology and Hepatology Commissionmentioning
confidence: 99%
“…One-off HCV screening and treatment of people aged 40-70 years is likely to be very cost-effective compared with the current practice of no screening. 409 Importantly, to reduce the incidence of HCV-related endstage liver-related complications and mortality, a national screening programme should include a national health policy aimed at managing HCV in the South Korean population.…”
Section: The Lancet Gastroenterology and Hepatology Commissionmentioning
confidence: 99%
“…However, some analysts have argued that this threshold is not valid for low‐income or mid‐income countries, and it should be lower for them . Thus, this paper used a conservative threshold of GDP‐per‐capita to define cost‐effectiveness and also to be consistent with previous studies in Korea …”
Section: Discussionmentioning
confidence: 87%
“…25 Thus, this paper used a conservative threshold of GDPper-capita to define cost-effectiveness and also to be consistent with previous studies in Korea. 26 A previous study from the USA on the cost-effectiveness of genotype 2 HCV therapeutics also showed that the comparative ICER of 12 weeks of SOF + RBV to 24 weeks of PR was $238 000 per QALY gained among treatment-naïve non-cirrhotic US patients, 27 which was not cost-effective. However, the comparative ICER of 12 weeks of SOF + RBV to 24 weeks of PR was $35 500 in cirrhotic patients and that of 16 weeks of SOF + RBV to 24 weeks of PR in treatment-experienced cirrhotic patients was $27 300, for which both cases were cost-effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost‐effectiveness of HCV screening is sensitive to the prevalence of asymptomatic HCV infection, the acceptability of the screening and treatment, treatment and care costs and affordability . Although the CEA of HCV screening is necessary for each country, there have been only a few CEA studies in Asia …”
Section: Introductionmentioning
confidence: 99%